Characteristic of Teaching Materials for Arabic Reading Skill with Inductive Approach - Himatul Istiqomah; Mohammad Jawad Habeeb Al-Badrani (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2020)
Himmati is deliberately created as a textbook modification to recognize the Qur'an prepared for beginners. This research aimed to describe the characteristics of teaching material contained in Himmati. This research was a qualitative approach and content analysis of the perspective of Thu’aimah. It also belonged to library research with the main data source is a book, named Himmati: Modifikasi Pembelajaran Dasar Mengenali al-Qur’an from volume 1 to volume 5. The results showed that: 1) Generally, the teaching materials in Himmati were divided into 5 volumes which were presented inductively, namely the introduction of letters, words, tajweed, gharib, and verses in the Qur’an. Specifically, the teaching materials in Himmati were divided into 7 volumes which were presented with examples from the Qur'an and colored in the order of the frequency of visible light, from red to violet. The 1st volume focused on pronunciation, the 2ndA volume was on short vowels, long vowels, nunation (tanwin), and original sukuun, the 2ndB volume was on non-original sukuun and shadda, the 3rdA volume was on the law of nuun sukuun, nunation, germination nuun and miim, the 3rdB volume was on the law of miim sukuun, definite article al, and madd, the 4th volume was on the rule of exception, and the 5th volume was on the stop sign. The teaching materials in Himmati presented for beginners level